Impact of online collaborative video annotation on STEM students' reflective thinking and academic self-discipline - Aguillon, Daniel Day De Vera (College of Education, University of the Philippines Diliman, 2019)
In recent years, technology-based education has been a word of mouth of educationalists. Contemporary researches focus on how technology-aided methodologies and approaches affect students academic achievement. More so, these studies also sought to examine possible associations with students behavior and attitude toward academic life. With all the demands of global competitiveness expected from 21st-century learners, consensus dissolves into educators and educationalists on how to respond to the effectiveness of emerging teaching approaches that involve technology. This study examines how online collaborative video annotation (OCVA) would affect students reflective thinking and academic self-discipline. The compares the effectiveness of the mentioned proposed approach to the conventional use of video-based lessons inside the classroom setting. This study also seminal works and pertinent information coming from reliable sources and references. The literature review was concentrated on merging ideas about how the mentioned educational concepts merge and possibly connive. It was found that, although reflection promotes the development of different aspects of learning like intelligences-intrapersonal and interpersonal skills, and effective domain academic self-regulation; there were extrinsic factors like critical thinking, teachers knowledge of pedagogical awareness and mastery of content and the homogeneity of the class have something to do about learning concepts in General Chemistry 1 course. This study is quasi-experimental in the form. The data presented in Chapter 4 were quantitative and qualitative in form. These data were then parallel using thematic analysis to come up with literature, context, and statistically rich information. The were ninety-eight STEM student-respondents who participated In this study. The data collection started with the pre-test of reflective thinking and academic self-discipline questionnaires to both sections to determine if there was no significant difference between sections. After getting the favorable results of non-significance and assumption of equal variance between two sections, using fishbowl method, the researcher picked the experimental group which would be exposed to the proposed teaching approach (OCVA) and followed by the control group which would be exposed to the conventional video-based lesson (COVL). The results of this study were obtained from using parametric (independent sample t-test) and non-parametric (MANN-Whitney U test) tests to get quantitative data and thematic analysis to develop which qualitative data. After the data gathering, the researcher assessed if the data gathered were parallel to each other. The research findings indicate that online collaborative video annotation (OCVA) does not significantly affect reflective thinking and academic self-discipline among students exposed to OCVA and COVL. However, the OCVA did affect the STEM student understanding-a component of reflective thinking, of lessons taught in general chemistry 1 course. The result was in line with the fact that students of the 21st century STEM students do understand texts and definitions shown in a learning video. However, the longevity of this acquired knowledge varies. Furthermore, reflective thinking collectively did not predict STEM students academic self-discipline. Conversely, the linear regression run to asses reflective thinking components did not contribute to further results of the study. It was found out that all reflective thinking components were associated with STEM students academic self-discipline in both video-based lesson (VBL) teaching approaches. Being a breakthrough study in the Philippine context, the researcher recommends this study to be used by school administrators, teacher education institutions, teachers and professors, curriculum developers and guidance counselors in developing a more technology-integrated, collaborative and active learning experience to STEM students. Future studies of the effectiveness of video annotation are also needed to explain how such a technology-aided teaching approach affects non-cognitive learning constructs such as self-motivation, self-regulation, self-efficacy and many more.